Absorbing aerosols over Asia – an inter-model and model-observation comparison study using CAM5.3-Oslo. Issue 1 (1st January 2021) - Frey, L.; Höpner, F.; Kirkevåg, Alf; Bender, F. A.-M.
Abstract: Aerosol absorption constitutes a significant component of the total radiative effect of aerosols, and hence its representation in general circulation models is crucial to radiative forcing estimates. We use here multiple observations to evaluate the performance of CAM5.3-Oslo with respect to its aerosol representation. CAM5.3-Oslo is the atmospheric component of the earth system model NorESM1.2 and shows on average an underestimation of aerosol absorption in the focus region over East and South Asia and a strong aerosol absorption overestimation in desert and arid regions compared to observations and other AeroCom phase III models. We explore the reasons of the model spread and find that it is related to the column burden and residence time of absorbing aerosols, in particular black carbon and dust. We conduct further sensitivity simulations with CAM5.3-Oslo to identify processes which are most important for modelled aerosol absorption. The sensitivity experiments target aerosol optical properties, and contrast their impact with effects from changes in emissions and deposition processes, and the driving meteorology. An improved agreement with observations was found with the use of a refined emission data set, transient emissions and assimilation of meteorological observations. Changes in optical properties of absorbing aerosols can also reduce the under- and overestimation of aerosol absorption in the model. However, changes in aerosol absorption strength between the sensitivity experiments are small compared to the inter-model spread among the AeroCom phase III models.